PENGARUH BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP INTENSI TURNOVER KARYAWAN UD INDIGO SEJAHTERA - OKTAVIANI, RENY (Jurnal Akuntansi AKUNESA, 2018)
A good of organization is supported by a good leadership and a good organizational culture as well. This study aims to determine the effect of organizational culture and leadership style on turnover intention of UD Indigo Sejahtera. Data collected through questionnaires. The populations of this research were all employees UD Indigo Sejahtera, totaling 45 employees. This study is using saturated method. Data analysis techniques used multiple linear regression analysis. Results showed the organizational culture has a significant and positive effect to the turnover intention UD Indigo Sejahtera and the leadership style has a not significant effect to turnover intention.Keywords: Organizational Culture, Leadership Style, and Turnover Intention.